2016
DOI: 10.1016/j.bpj.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Binding by TRBP-dsRBD2 Does Not Induce Bending of Double-Stranded RNA

Abstract: Protein-nucleic acid interactions are central to a variety of biological processes, many of which involve large-scale conformational changes that lead to bending of the nucleic acid helix. Here, we focus on the nonsequence-specific protein TRBP, whose double-stranded RNA-binding domains (dsRBDs) interact with the A-form geometry of double-stranded RNA (dsRNA). Crystal structures of dsRBD-dsRNA interactions suggest that the dsRNA helix must bend in such a way that its major groove expands to conform to the dsRB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Acevedo et al used MD simulations and isothermal titration calorimetry (ITC) measurements to study the complex of dsRBD2 domain of the HIV-1 TAR RNA binding protein (TRBP) with dsRNA (TRBP-dsRBD2/dsRNA) . An earlier X-ray structure of this complex suggested that the RNA helix becomes bent upon protein binding .…”
Section: Simulations Of Specific Rna Systemsmentioning
confidence: 72%
See 1 more Smart Citation
“…Acevedo et al used MD simulations and isothermal titration calorimetry (ITC) measurements to study the complex of dsRBD2 domain of the HIV-1 TAR RNA binding protein (TRBP) with dsRNA (TRBP-dsRBD2/dsRNA) . An earlier X-ray structure of this complex suggested that the RNA helix becomes bent upon protein binding .…”
Section: Simulations Of Specific Rna Systemsmentioning
confidence: 72%
“…Acevedo et al used MD simulations and isothermal titration calorimetry (ITC) measurements to study the complex of dsRBD2 domain of the HIV-1 TAR RNA binding protein (TRBP) with dsRNA (TRBP-dsRBD2/dsRNA). 1083 An earlier X-ray structure of this complex suggested that the RNA helix becomes bent upon protein binding. 1084 However, on the basis of the simulations and ITC data, the authors suggested that the helix does not actually bend, that TRBP preferentially binds to an ideal A-RNA helix, and that the helical geometry is not appreciably altered upon protein binding.…”
Section: Simulations Of Specific Rna Systemsmentioning
confidence: 94%
“…Such defects also lead to change in the spread of the minor-major-minor groves of the dsRNA (each represented by a unique structure defined by Euler angles (Bailor, Sun and Al-Hashimi, 2010)), thereby affecting the interaction between the dsRBD and dsRNA. Acevedo et al have shown that interaction between dsRBD2 of TRBP does not lead to a significant conformational change in the substrate dsRNA (Acevedo et al, 2016). Thus, to effectively and efficiently target a dsRNA from the wide pool of structurally different dsRNAs in the cellular matrix, dsRBDs must adapt itself to accommodate the conformational heterogeneity of the target dsRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…3B ) along with the elongated N- and C-terminal loops in the majority of the ribosomal proteins, which are stabilized while forming the ribosomal assemblies 23 . In another case, the positive value of average δA R at the interfaces in class C complexes can be supported by the molecular dynamics simulation study of double-stranded RNA, which explains that a stable A-form geometry of duplex RNA undergoes negligible changes while interacting with double-stranded RNA binding domains 24 .…”
Section: Discussionmentioning
confidence: 83%